Interaction of malaria and HIV in Africa. (3rd June 2009) - Reithinger, Richard; Kamya, Moses R; Whitty, Christopher JM; Dorsey, Grant; Vermund, Sten H
Abstract : Is well known at a biological and health systems level, but often ignored